Upaya Guru Bimbingan dan Konseling dalam Meningkatkan Prestasi Belajar Siswa di Sekolah Menengah Pertama - Nalley, Jean karolin (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
Student learning achievement is an important indicator in measuring the success of the educational process in schools. This research aims to identify and analyze the efforts made by Guidance and Counseling teachers in improving student learning achievement at the Junior High School level. This research uses a qualitative approach with a case study method at one of the State Junior High Schools. Data were collected through in-depth interviews with GC teachers, observation of GC service activities, and analysis of GC program documents. The results showed that GC teachers implement various comprehensive strategies including orientation services for new student adaptation, information services about effective learning techniques, group guidance services to increase learning motivation, individual counseling to overcome personal problems that interfere with learning, and collaboration with subject teachers and parents. These programs have proven effective in increasing learning motivation, reducing academic problems, and ultimately having a positive impact on improving student learning achievement.